1998
DOI: 10.1111/j.1600-065x.1998.tb01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell differentiation: insights from knockout and transgenic mouse models and in vitro systems

Abstract: In the last few years, the routine development of knockout and transgenic mice and the ease with which rare progenitor populations can be isolated from hematopoietic organs and cultured in vitro has facilitated significant advances in understanding the lineage and development of natural killer (NK) cells. Fluorescence-activated cell sorter analyses have identified a common lymphoid progenitor capable of giving rise to NK, T, and B cells, confirming the lymphoid origin of NK cells. Knockout and transgenic mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
83
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 124 publications
3
83
1
Order By: Relevance
“…For example, IL-15-deficient mice lack NK1.1 ϩ cells (3), indicating that IL-15 is essential for NK cell development in mice. The requirement of IL-15 for mouse NK cell development has also been demonstrated by other studies (4,5). In humans, IL-15 is considered to be required for in vitro NK cell development and virtually most current protocols for human NK cell differentiation culture depend on IL-15.…”
mentioning
confidence: 69%
“…For example, IL-15-deficient mice lack NK1.1 ϩ cells (3), indicating that IL-15 is essential for NK cell development in mice. The requirement of IL-15 for mouse NK cell development has also been demonstrated by other studies (4,5). In humans, IL-15 is considered to be required for in vitro NK cell development and virtually most current protocols for human NK cell differentiation culture depend on IL-15.…”
mentioning
confidence: 69%
“…As indicated by in vivo studies, patients who demonstrate Th2 dominance tend to develop chronic infection, whereas those with a Th1 phenotype can clear Of the ISGs analyzed, IL-15, a unique target of IRF-1, was also substantially reduced in both hepatic and T cells expressing either the entire HCV replicon or the structural proteins, and to our knowledge this is the first study reporting a repression of IL-15 in cells bearing the entire HCV replicon. IL-15 is involved in the activation and homeostatic maintenance of cells of both the innate and adaptive immune systems, playing a key role in CD8 ϩ T-cell homeostasis by promoting survival or proliferation of naive and memory phenotype CD8 T cells and in NK cell development, maturation, and survival (14,40,80). Notably, it has been reported that impaired IL-15 production is one of the mechanisms of the aberrant response of DC to IFN in HCV-infected patients (28).…”
Section: Discussionmentioning
confidence: 99%
“…18,22 Neither IL-12 nor IL-18 seem to be essential for NK cell development, since both IL-12-deficient and IL-18-deficient mice show normal NK 1.1 þ cell development. 32 As is the case for IL-12-deficient and IL-18-deficient mice, the B6-mi/mi mice showed normal NK 1.1 þ cell development and significantly reduced NK activity. 9,10 However, in contrast to the IL-12-deficient and IL-18-deficient mice, the NK activity of B6-mi/mi mice was not recovered even after daily intraperitoneal injection of IL-18 (1000 ng) or IL-12 (100 ng) for 2 days, 22 (our unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Several cytokines play important roles in NK cell development and activity (reviewed in Williams et al 32 and Colucci et al 33 ). For example, Flt3 (FMS-like tyrosine kinase 3) ligand, 34 c-kit tyrosine kinase ligand, 35 and IL-7 36 are important for the early stages of NK cell development.…”
Section: Discussionmentioning
confidence: 99%